Pengaruh Model Problem Based Learning Berbantuan Lembar Kerja Peserta Didik Terhadap Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Riska Nur Amaliya; Hery Kresnadi; Asmayani Salimi (Journal on Education, 2024)
This study aims to analyze the effect of using the PBL model assisted by LKPD on the learning outcomes of IPAS of grade IV students. The population in this study were 65 students of class IV SDN 17 Pontianak Kota. The withdrawal of samples in this study used probability sampling with the type of sample random sampling, which provides an opportunity for all members of the population to become samples. Data collection was done using measurement/test with multiple choice questions. Based on data analysis, the average post-test for the experimental class was 80.25 while the average post-test for the control class was 76.37. Based on the results of the t test calculation, obtained tcount = 4.8156 and ttable = 1.999 means tcount > ttable, then Ha is accepted, proving that there is an effect of using the PBL model assisted by LKPD on IPAS learning outcomes. The results of the calculation of effect size (ES), obtained ES = 0.39 included in the medium criteria. Thus, it can be concluded that the use of the PBL model assisted by LKPD has a positive effect on the learning outcomes of IPAS grade IV students.